Harmonized system of quality assessment for electronic components. Fixed capacitors for use in electronic equipment. Blank detail specification. Fixed polypropylene film dielectric metal foil d.c. capacitors. Assessment level E. (15th February 1993) - British Standards Institution,
No abstract available